Biogeographic Patterns of Ectomycorrhizal Fungal Communities Associated With Castanopsis sieboldii Across the Japanese Archipelago - Matsuoka, Shunsuke; Iwasaki, Takaya; Sugiyama, Yoriko; Kawaguchi, Eri; Doi, Hideyuki; Osono, Takashi (Frontiers in Microbiology, 2019)
Biogeographic patterns in ectomycorrhizal (ECM) fungal communities and their drivers have been elucidated, including effects of host tree species and abiotic (climatic and edaphic) conditions. At these geographic scales, genotypic diversity and composition of single host tree species change with spatial and environmental gradients, reflecting their historical dispersal events. However, whether the host genotypes can be associated with the biogeographic patterns of ECM communities remains unclear. We investigated the biogeographic pattern of ECM fungal community associated with the single host species Castanopsis sieboldii (Fagaceae), whose genotypic diversity and composition across the Japanese archipelago has already been evaluated. ECM communities were investigated in 12 mature Castanopsis-dominated forests covering almost the entire distribution range of C. sieboldii, and we quantified the effect of host genotypes on the biogeographic pattern of ECM fungal communities. Richness and community composition of ECM fungi changed with latitude and longitude; these biogeographic changes of ECM community were significantly correlated with host genotypic variables. Quantitative analyses showed a higher relative explanatory power of climatic and spatial variables than that of host genotypic variables for the biogeographic patterns in the ECM community. Our results suggest historical events of host dispersal can affect the biogeographic patterns of the ECM fungal community, while their explanation power was lower than that for climatic filtering and/or fungal dispersal.